Public Budgeting Reform in China: Theory and Practice - Liu, Xiaonan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book introduces the theory and practice of Chinese public budget reform, including the manner and implications of public budget reform, the role and status of central government and local governments in budget reform, as well as the latest achievements of China$1 (Bs local government public budget reform. The authors of this book are all researchers who have witnessed Chinese public budget reform.s
How and Where Government Spends Money: Public Budgeting Reform and Citizen Participation -- Institutional Reform and Innovation in the Public Financing System -- ays to Promote Public Budgeting Reform -- A Constitutional Perspective on the Financial Transfer Payment System in China -- A Constitutional Review of Division of Fiscal Responsibilities between Central and Local Governments -- Review of Public Budgeting Reform in Minhang -- Role of People$1 (Bs Congress in Minhang Performance Budgeting Reform -- Thoughts on Participatory Budgeting in China: Minhang Case Study -- Department Performance Evaluation in Minhang Budgeting Reform -- Results-oriented Performance Budgeting Management in Minhang -- From Government Budget to Public Budget: Participatory Budgeting Practices in Wenling City -- Budget Management, Examination and Oversight: Jiaozuo City Case Study -- Lessons from Nanhai District$1 (Bs Experience with Financial Performance Management.s
Keywords: Public finance; Economic policy; Economic growth; Economics; Public Economics; Economic Policy; Economic Growth; Electronic books